Legal Analysis Of Legal Protection Of Parties In Multipurpose Financing By Means Of Fund Facilities at PT. Federal Internasional Finance (FIF Group) Tembung Branch, Deli Serdang - Hutabarat, Sonita. E; Ginting, Budiman; Sidabariba, Burhan (Jurnal Ilmu Sosial Mamangan, 2025)
One of the financing institutions in Indonesia is the Federal International Finance (FIF GROUP) company. PT. Federal International Finance Tembung Branch, Deli Serdang City is one of the company's branches engaged in multipurpose financing by means of funding facilities or also called Danastra. In terms of lending, FIF offers loan products using collateral in the form of BPKB (Motor Vehicle Ownership Book), financing activities are carried out through a credit provision system where payments by consumers are made in installments or periodically. This study uses a normative legal research method, namely research conducted by examining library materials or secondary materials. The purpose of this study is to determine the legal protection of the parties in multipurpose financing by means of funding facilities at PT. Federal International Finance (FIF Group) Tembung Branch, Deli Serdang. Often the provisions or rules that have been made and agreed upon by both parties in practice do not meet and do not comply with the contents of the agreement, whether it is intentional or due to negligence of the parties, where the agreement implemented is not in accordance with what is desired. In addition, there is also a factor that is caused by consumers not knowing the standard regulations that have been made by the creditor, because they are more concerned with the goods they take rather than paying attention to the regulations set out in the agreement, so that there is a default in the implementation of the agreement.